Neoclassical Music in America : Voices of Clarity and Restraint - Tobin, R. James (Modern traditionalist classical music., 2014)
In Neoclassical Music in America: Voices of Clarity and Restrain, music reviewer and scholar, R. James Tobin explores the origins and fate of neoclassicism, arguing how efforts to define musical neoclassicism as a style largely fail because of the stylistic diversity of the music that fall within its scope. Tobin surveys the careers of various figures, drawing especially on early reviews of performances before offering his own critical assessment of individual works. His examination includes such European influencers, as Igor S.